Antibody-Drug Conjugates vs. Traditional Biologics: A Comparative Analysis of Rheumatic Disease Management - Sheikh, Mujibullah; Roy, Pollob; Jirvankar, Pranita (International Journal of Pharmaceutical Investigation, 2025)
The review article deals with the possibility of the use of Antibody-Drug Conjugates (ADCs) for the treatment of rheumatic diseases. The introduction emphasizes the difficulty of chronic autoimmune diseases’ management and identifies the shortcomings of the current approach of using Disease-Modifying Antirheumatic Drugs (DMARDs) and biologies. ADCs appear as an attractive solution which links a monoclonal antibody and a cytotoxic component to recognize cancer cells specifically and in so doing minimize systemic toxicity. In the overview of ADCs and traditional biologics these new therapies are compared to traditional biologics with a focus on the major developments in the field of ADC since the 1st ADC approval in 2000. The properties it addresses cover the structural characteristics of ADCs in terms of monoclonal antibodies, cytotoxic components and linkers. The action section is describing how ADCs convey selectively to specific antigens on cancer cells, internalization through endocytosis. This process results in the generation of cytotoxic agents within tumor cells that proclaim apoptosis and are harmless to the other tissues. The problem of a bystander effect, under which released payloads impact non-target cells nearby, is also considered. The review also assesses the effectiveness and safety of approved ADCs in the US FDA: presenting clinical trial results and patients’ outcomes. It then considers difficulties in the generation of next-generation ADCs and their further case usage in clinical practice and points out the need for further research to enhance the effectiveness of these therapies for rheumatic diseases. In conclusion, this article seeks to demystify areas of uncertainty and lay a robust background for subsequent investigations that will enhance treatment plans for rheumatic condition patients.
Keywords: Antibody-Drug Conjugates (ADCs); Cytotoxic Payload; Disease-Modifying Antirheumatic Drugs (DMARDs); Monoclonal Antibodies and Rheumatic Diseases